Analysis Factor of Diarrhea with Latrine Ownership and Clean Water Availability in Indonesia: Meta Analysis 2016-2021 - Soehartini, Soehartini Toemiran; Taufik Ikhtiar, Erwan; Dimjati Lusno, M. Farid; Azizah, R.; Kurniawan, G. (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
The study examines the relationship between Diarrhea, Latrine Ownership, and Clean Water Availability in Indonesia, specifically focusing on 2016 to 2021. According to the 2018 RISKESDAS, the age group with the highest diarrhea prevalence, as health workers diagnosed, was 1 to 4 years (1.5%), followed by infants (9%). West Java Province had the highest prevalence of diarrhea by province, with a rate of 186.809. The purpose is to analyze data related to latrine ownership and the availability of clean water about the incidence of diarrhea in Indonesia. The method is meta-analysis. We used a cross-sectional approach to collect secondary data from articles from March to April 2023. The results show that ownership of a latrine that does not meet the requirements is 2,013 times more likely to cause diarrhea than ownership of a latrine that meets the requirements. From the results of the meta-analysis of the variable availability of clean water, it is known that the availability of clean water that does not meet the requirements is 1,858 times more at risk of causing diarrhea than the availability of clean water that meets the requirements. The conclusion is that the variable that has the most significant influence on latrine ownership and the availability of clean water is latrine ownership. We suggest minimizing risk factors by counseling the community, emphasizing the importance and benefits of having healthy latrines that meet requirements and the availability of clean water to prevent diarrheal disease.